The Role of the place of arbitration in international commercial arbitration proceeding; Turkey as a place of arbitration - (:unkn) unknown (My University, 2011)
0

In recent years, arbitration proceeding has become a common dispute resolution method, particularly in the field of international commercial disputes. One of the reasons is that the parties want to resolve their dispute in privacy and obtain an enforceable award as soon as possible. The parties’ tendency to apply arbitration proceeding has forced the states to review their arbitration law and procedural law. In this way the countries want to make their states an attractive place for the arbitral proceeding. As it will be seen in the following parts, the place of arbitration has a vital role over the arbitral proceeding. It has some effects over the legal issues, such as the determination of the arbitrators, enforcement of the awards, and it also has an impact over the practical issues such as accommodation, visa issues. Because of those crucial effects of the place of arbitration, the parties have to be sure that they have chosen the best suitable place as the place of arbitration. In order to set light to the parties and practitioners, in this article, the role of the place of arbitration will be explained and Turkey will be evaluated as a place of arbitration.
Keywords: Hukuk